Report of the Task Force in Formulating Action Plan for Removal of Arsenic Contamination in West Bengal - Planning Commission (Planning Commission, 2007)
Arsenic contamination in West Bengal affects millions, posing serious health risks such as skin lesions, cancer, and developmental issues. Groundwater in multiple districts contains arsenic levels far exceeding WHO limits, necessitating urgent intervention. The Task Force report identifies both short-term and long-term strategies, including community-level arsenic treatment plants, surface water use, and rainwater harvesting. Various removal technologies—coagulation, adsorption, reverse osmosis, biological, and electrochemical methods—were evaluated for effectiveness, cost-efficiency, and operational feasibility. Challenges include inadequate community engagement, maintenance, and chemical supply. Recommendations stress community-centric operations, rigorous technology assessment, and awareness campaigns to ensure sustainable access to safe drinking water.
Government Of India Planning Commission Yojna Bhawan New Delhi (July 2007)
Government Of India Planning Commission Yojna Bhawan New Delhi (July 2007)
Keywords: Arsenic Contamination; West Bengal; Groundwater; Health Risks; Water Treatment; Removal Technologies; Community Awareness; Sustainable Solutions; Public Health; Rainwater Harvesting